2007
DOI: 10.1124/mol.106.033100
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening for Small-Molecule Activators of Neutrophils: Identification of NovelN-Formyl Peptide Receptor Agonists

Abstract: We screened a chemolibrary of drug-like molecules for their ability to activate reactive oxygen species (ROS) production in murine phagocytes, and we identified 26 novel compounds with potent neutrophil activating properties. We used substructure screening, fragment-focusing, and structure-activity relationship analyses to further probe the parent library and defined at least two groups of activators of ROS production in murine neutrophils: t-butyl benzene and thiophene-2-amide-3-carboxylic ester derivatives. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 36 publications
3
95
0
Order By: Relevance
“…In order to find agonists with this potency, we screened a library of small compounds and several ligands for FPR2 with varying EC 50 values were identified. The identification of small-molecule ligands represent an attractive approach to analyze structure and function of FPRs, and in line with this several research articles using the same approach have been published during the last couple of years [16,[38][39][40]. Of the compounds that we used and found to activate human neutrophils to produce/release superoxide anions, 5 (4 unique and one enantiomer) have been described earlier.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In order to find agonists with this potency, we screened a library of small compounds and several ligands for FPR2 with varying EC 50 values were identified. The identification of small-molecule ligands represent an attractive approach to analyze structure and function of FPRs, and in line with this several research articles using the same approach have been published during the last couple of years [16,[38][39][40]. Of the compounds that we used and found to activate human neutrophils to produce/release superoxide anions, 5 (4 unique and one enantiomer) have been described earlier.…”
Section: Discussionmentioning
confidence: 81%
“…When investigated, the functional repertoire triggered by small non-peptide agonists such as the Quinazolinonoe (Quin-C1) derivatives that selectively bind FPR2 [15],AG14 that selectively binds FPR1 [16], and pyrazolone that binds both receptors [17], resembles that of the pro-inflammatory peptides and not that of the anti-inflammatory agonists. Using a chemolibrary screening approach it was recently shown that agonists of FPR1/FPR2 include compounds with wide chemical diversity [18].…”
Section: Introductionmentioning
confidence: 99%
“…We recently screened a chemolibrary of drug-like molecules for their ability to activate phagocytes and identified several novel small-molecule FPR/FPRL1 agonists (Schepetkin et al, 2007). In the present studies, analysis of the ability of these compounds to induce phagocyte TNF-␣ production showed that five of these compounds induced modest levels of TNF-␣ by macrophages.…”
mentioning
confidence: 93%
“…All animal use was conducted in accordance with a protocol approved by the Institutional Animal Care and Use Committee at Montana State University. Bone marrow leukocytes were flushed from tibias and femurs of BALB/c mice with HBSS Ϫ supplemented with 0.1% BSA and 1% glucose and the neutrophils were purified on Percoll density gradients, as described previously (Schepetkin et al, 2007).…”
mentioning
confidence: 99%
“…Murine J774.A1 macrophages (1.5×10 5 cells/well) were incubated with various concentrations of polysaccharide fractions or positive control (LPS) for 24 hr. After incubation, 100 μl of culture supernatant (removed for NO analysis) was replaced by an equal volume of HBSS supplemented with 25 μM L-012 and 5 μg/ml HRP, as described previously [17]. The reaction was monitored on a Fluoroscan Ascent FL microtiter plate reader (ThermoElectron, Milford, MA) at 37°C.…”
Section: Analysis Of Ros Productionmentioning
confidence: 99%